Identifying users’ engagement in e-commerce - Lizawati @ Rosclaritha Maidom; Aslina Baharum; Dina @ Nina Mohd Nizam (MNNF Publisher, 2021)
The digital age has produced a plethora of diverse websites for web users to connect and use. Although E-Commerce advancement has grown immensely and became a valuable channel for the transaction of selling and purchasing activity between seller and customers, E-Commerce companies are faced with a highly competitive environment today with the flooding emergence of business going digital. An effective website is a significant factor in attracting and retaining customers’ absorption to promote purchasing behaviour. Additionally, user engagement is often associated with the workflow of E-Commerce due to its ability in influencing customers’ satisfaction. However, there is a lack of quantitative studies focusing on the construct of customer engagement observed. For these reasons, there is a need for the exploration to concentrate on the antecedents and consequences of the construct of user engagement to get an in-depth clarity on the aspect. Literature reviews performed demonstrates very few empirical studies focusing on E-Commerce as a contextual periphery of optimization of user engagement. Although user engagement has been widely highlighted in various fields for its significance, it is still a challenge for an E-Commerce business to optimize it as to lack of reference effectively. Theoretically, a good design constitutes factors of users’ satisfaction assimilation requirements and technical implementation. Therefore, understanding and fulfilling people’s demand is a fundamental design concept required to be implemented. Thus, this study aims to identify the elements of user engagement in E-Commerce through a preliminary review study. The results of the study show the identified and listed users’ engagement elements and the design elements that contributes to the user engagement elements. The extracted result of the study will benefit researchers and designers to produce an effective E-Commerce website that promotes engagement with the integration of user engagement elements on the development. The implementation shall be useful to be used as a guidance and improvement reference.